2023
DOI: 10.3390/nu15020366
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Mediterranean Diet for 6 Months Improves the Dietary Inflammatory Index in a Western Population: Results from the MedLey Study

Abstract: Increasing evidence supports that a higher dietary inflammatory index (DII®) score is associated with inflammation and cardiovascular disease (CVD) risk, events, and mortality. This randomized trial sought to determine if a change to a Mediterranean diet resulted in a reduction in the DII score, and then it evaluated the relationship between the DII and cardiometabolic outcomes following the administration of a traditional Mediterranean diet in older Australian adults. A total of 152 Australian adults (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In summary, the MedDiet, known for its anti-inflammatory effects, has been linked to a decrease in the DII score. A randomized controlled trial conducted among older Australians showed that adherence to the MedDiet for 6 months significantly reduced DII scores ( 47 ). This decrease in DII scores implies a potential reduction in inflammation, which could have a positive impact on AR.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the MedDiet, known for its anti-inflammatory effects, has been linked to a decrease in the DII score. A randomized controlled trial conducted among older Australians showed that adherence to the MedDiet for 6 months significantly reduced DII scores ( 47 ). This decrease in DII scores implies a potential reduction in inflammation, which could have a positive impact on AR.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-based diets that are rich in vegetables, fruits, whole grains, nuts, and olive oil, such as the Mediterranean diet, have been shown to reduce inflammation and lower the risk of cardiovascular disease [ 39 ]. Clark et al conducted a study to investigate the effect of a Mediterranean diet intervention on cardiometabolic outcomes in healthy older adults [ 40 ]. The study demonstrated that the intervention, which lasted for 6 months, significantly reduced the dietary inflammatory index (DII) scores compared to a habitual Australian diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed association between sexual health, improved metabolic syndrome components, and the MD may suggest the significant role of antioxidant components. The pro-inflammatory state developed as a result of chronic oxidative stress is one of the causes of the development of conditions that are categorized as metabolic syndrome [76,79].…”
Section: Possible Mechanismmentioning
confidence: 99%